Komitmen tanpa Konflik: Tawaran Teologi Pluralisme Kristiani - Samosir, Leonardus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2005)
Religions are always in tension between their claims of universality and the fact of  their particularity.  The potential of conflict arises precisely when the particular religion claims  a universal truth.  Christian theology of  religious pluralism has managed to neutralize the tension by emphasizing the commitment to particular religion and at the  same time  the commitment to universal world problems. Such theological vision is supported  by a philosophical reflection that sees truth as  “revealed in“ but not  “exclusively possessed“ by the particularity. In itself  the truth remains transcendental, yet it shows its “traces“ in the positive outcomes of the particular.